The iPhone developer's cookbook : building applications with the iPhone SDK - Sadun, Erica (Developer's library., 2009)
"This book would be a bargain at ten times its price! If you are writing iPhone software, it will save you weeks of development time. Erica has included dozens of crisp and clear examples illustrating essential iPhone development techniques and many others that show special effects going way beyond Apple's official documentation."--Tim Burks, iPhone Software Developer, TootSweet Software "Erica Sadun's technical expertise lives up to the Addison-Wesley name. The iPhone Developer's Cookbook is a comprehensive walkthrough of iPhone development that will help anyone out, from beginners to more experienced developers. Code samples and screenshots help punctuate the numerous tips and tricks in this book." --Jacqui Cheng, Associate Editor, Ars Technica "We make our living writing this stuff and yet I am humbled by Erica's command of her subject matter and the way she presents the material: pleasantly informal, then very appropriately detailed technically. This is a going to be the Petzold book for iPhone developers." --Daniel Pasco, Lead Developer and CEO, Black Pixel Luminance " The iPhone Developer's Cookbook: Building Applications with the iPhone SDK should be the first resource for the beginning iPhone programmer, and is the best supplemental material to Apple's own documentation." --Alex C. Schaefer, Lead Programmer, ApolloIM, iPhone Application Development Specialist, MeLLmo, Inc "Erica's book is a truly great resource for Cocoa Touch developers. This book goes far beyond the documentation on Apple's Web site, and she includes methods that give the developer a deeper understanding of the iPhone OS, by letting them glimpse at what's going on behind the scenes on this incredible mobile platform." --John Zorko, Sr. Software Engineer, Mobile Devices The iPhone and iPod touch aren't just attracting millions of new users; their breakthrough development platform enables programmers to build tomorrow's killer applications. If you're getting started with iPhone programming, this book brings together tested, ready-to-use code for hundreds of the challenges you're most likely to encounter. Use this fully documented, easy-to-customize code to get productive fast--and focus your time on the specifics of your application, not boilerplate tasks. Leading iPhone developer Erica Sadun begins by exploring the iPhone delivery platform and SDK, helping you set up your development environment, and showing how iPhone applications are constructed. Next, she offers single- ...